The influence of safety climate on safety performance among workers of a food emulsifiers company in Malaysia - Thurai, Krishanan (2018)
This study aimed to determine the relationship between safety climate and safety performance in Danisco Malaysia Sdn. Bhd. Six dimensions of safety climate were studied in this research namely management safety practices, safety attitude, safety training, supervisory safety practices, the involvement of co-workers, and job safety. In order to achieve the objectives of the study, 146 sets of questionnaires were distributed to the staff in the operation department of Danisco Malaysia. Quantitative data were analyzed using SPSS software. Pearson correlation test found a significant positive relationship for five out of six dimensions of safety climate against with safety performance. The five significant dimensions are management safety practices, safety training, supervisory safety practices, the involvement of co-workers, and job safety. However, safety attitude was found to have an insignificant relationship with safety performance. Multiple regression tests revealed that safety climate dimensions significantly influence safety performance. Finally, the implications of the study are discussed to provide recommendations and guidelines for future researches.